2016
DOI: 10.21653/tfrd.272249
|View full text |Cite
|
Sign up to set email alerts
|

Pes Planus Olan ve Olmayan Erkeklerde Fiziksel Uygunluğun Değerlendirilmesi

Abstract: Amaç: Bu çalışma, pes planus olan ve olmayan erkeklerde fiziksel uygunluk parametrelerini değerlendirmek amacıyla yapılmıştır.Yöntemler: Çalışmaya yaşları 18 -45 yıl arasında değişen, Feiss çizgisine göre deformite derecesi 2 ve üstünde olan pes planus tanısı konulmuş 50 gönüllü (deney grubu) ve 50 sağlıklı birey (kontrol grubu) alınmıştır. Bireylerin demografik özellikleri ve fiziksel uygunluk testleri değerlendirilmiştir. Katılımcıların fiziksel uygunluklarının değerlendirilmesinde postür analizi, kısalık te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
6
1
2
Order By: Relevance
“…In our study, it was found that dynamic balance performance decreased with increasing ND value in individuals with flexible pes planus. There are many studies in the literature examining the effect of balance in individuals with pes planus (4,17,31). Kızılcı and Erbahçeci found that the single leg standing time was negatively affected according to the pes planus severity (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, it was found that dynamic balance performance decreased with increasing ND value in individuals with flexible pes planus. There are many studies in the literature examining the effect of balance in individuals with pes planus (4,17,31). Kızılcı and Erbahçeci found that the single leg standing time was negatively affected according to the pes planus severity (17).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies in the literature, the negative effects of pes planus on lower extremity physical performance have been reported. (4,16,17). However, revealing the effect of pes planus severity on performance in individuals with pes planus may guide in determining the risk factors of inadequate lower extremity performance in these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study, postural deviation and muscle shortness (in the gastrosoleus muscle group) were higher in the group with PP, while the time to stay in equilibrium was found to be lower. It was concluded that pes planus deformity negatively affects physical fitness in men [ 33 ]. A study conducted in 2018 examined the relationship between increased pronation in the hindfoot and physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Pes planusu olan ve olmayan bireylerde tibialis posterior ve peroneal kas Çalışmamız pes planusu olan bireylerde pes planusu olmayanlara göre pelvik inklinasyon açısı ve bel ağrısının artmış olduğunu gösterildi. Literatürde pes planusun, pelvik inklinasyon açısı ve lumbal lordozu artırdığını ve bel ağrısına neden olduğunu gösteren çalışmalar bulunmaktadır (33)(34)(35)(36). Askerlerde yapılmış olan bir çalışma, orta ve şiddetli pes planusun ön diz ağrısı ve bel ağrısı ile ilişkili olduğunu bildirmiştir (19).…”
Section: Discussionunclassified